Sensory eye balance in surgically corrected intermittent exotropes with normal stereopsis - Feng, Lixia (Nature Publishing Group, 2015)
Surgery to align a deviated or strabismic eye is often done for both functional as well as cosmetic reasons. Although amblyopia is often an impediment to regaining full binocularity in strabismics in general, intermittent exotropes, because their deviation is intermittent, have no amblyopia and some degree of stereopsis. Binocular function, including a balanced ocular dominance, could be expected to be normal after surgical correction if normal levels of stereopsis and visual acuity are postsurgically achieved. Here we used a binocular phase combination paradigm to quantitatively assess the ocular dominance in a group of surgically corrected intermittent exotropes who have normal stereo and visual acuity as defined clinically. Interestingly, we found significant interocular imbalance (balance point < 0.9) in most of the surgically treated patients (8 out 10) but in none of the controls. We conclude that the two eyes may still have a residual sensory imbalance in surgically corrected strabismus even if stereopsis is within normal limits. Our study opens the possibility that a further treatment aimed at re-balancing the ocular dominance might be necessary in surgically treated intermittent exotropia to provide more efficient binocular processing in the long term.